Investigation of Sleep Hygiene and Quality of Life in Nursing Students - Betül Bayrak; Beyza Alev (CURARE Journal of Nursing)
Objective: To determine the level of sleep hygiene and quality of life in nursing students and to investigate the relationship between them. Material and Methods: The descriptive and correlational type research was conducted between June 1 and July 1, 2023 with 324 students (N=475) from all classes of the nursing department of a university who agreed to participate in the research without any sample selection. Data were collected with the “Personal Information Form”, “Sleep Hygiene Index (SHI)” and “SF-36 Quality of Life Scale”. Data analysis was performed on the computer with the SPSS-26 statistical package program. Results: The mean age of the students was 20.5 ± 1.7, 76.2% were female, 28.7% were first year students. The students’ SHI score average was 33.6 ± 6.2, and the SF36 scale sub-dimensions score were; physical function 91.5±12.5, physical role difficulty 67.7±34.9, emotional role difficulty 50.1±42.2, vitality 47.1±17.0, social function 74.8±18.5, pain 64.1±21.6, mental health 57.5±16.7 and general health perception 57.2±16.2. It was found that a statistically significant difference between students’ grade level, financial situation, general sleep patterns, general health status, general quality of life and SHI score averages (p<0.01). Between the students’ SHI scores and the SF36 scale, all sub-dimensions except physical function were obtained a negative moderately significant relationship (p<0.01). Conclusion: In the study, it was concluded that the sleep hygiene of the nursing students was at a moderate level, in the quality of life sub-dimensions physical function was the highest and vitality was the lowest, and a negative relationship between the quality of life sub-dimensions except for physical function, and sleep hygiene.